Dynamic response analysis of isolated curved beam bridge under multi-dimensional non-stationary random excitation considering the torsion component. Issue 1 (1st January 2022) - Li, XM; Wang, JC; Pu, K; Mu, BH
Abstract: The coupling effect of bending and torsion caused by plane irregularity of the isolated curved beam bridge makes its seismic response more complex than that of the isolated straight beam bridge. In order to study the influence of multi-dimensional non-stationary random excitation considering torsion component on seismic response of tqiongw@mls.sinanet.com he isolated curved beam bridge. The classical Bouc-Wen model was used to simulate the hysteretic characteristics of the curved beam bridge, and the nonlinear dynamic equation considering the eccentricity of superstructure was established. The pseudo excitation was transformed into harmonic external load by Euler formula, and combining with the precise integration method, the precise integration forms of the special solution under different modulation functions were derived. By using these integral forms to solve the response at each time, the time-varying variance of displacement of the isolated curved beam bridge under multi-dimensional non-stationary random excitation was obtained, and the law of time-varying variance of displacement, including the upper and lower structures of the isolated curved beam bridge, was analyzed with different deck width, curvature radius and yield ratio of bearing. The results show that the multi-dimensional non-stationary random excitation with torsion component has significant influence on the seismic response of the isolated curved beam bridge. Under the rare non-stationary random excitation, the dynamic response of the isolated curved beam bridge presents strong non-stationarity, and the time-lag phenomenon is apparent. For the isolated curved beam bridge with large deck width and small yield ratio of bearing, the influence of non-stationary random excitation on the structure is particularly obvious. The influence of non-stationary random excitation considering torsion component on dynamic response of the isolated curved beam bridge with large deck width, small curvature radius and large yield ratio of bearing is more significant.